Ripensare modelli e prassi di valutazione della qualità nella scuola dell'infanzia. Una ricerca esplorativa nel campo della «Formative Educational Evaluation» - Ira Vannini; Rossella D'Ugo (LED Edizioni Universitarie, 2011)
Rethinking Quality Evaluation Models and Practices in Kindergartens. An Explorative Study in the Field of Formative Educational Evaluation This article presents the three-year progress and main results of an educational evaluation study conducted with a formative-research perspective (Becchi et al., 1997; Lodini & Vannini, 2006) in the kindergartens of a Bologna neighbourhood. Starting from a critical use of the Sovasi Scale (Harms & Clifford, 1994) and from the methodological procedures of the «Formative Evaluation Model» (Bondioli & Ferrari, 2004), this study led to various results with regard to both external and internal evaluation. Regarding external evaluation, Sovasi profiles of 15 kindergarten sections were observed, highlighting the differences between schools and establishing the quality practices characterising local planning and educational decisions and which constitute an educational asset of the municipality of Bologna. With regard to internal evaluation, the 15 kindergarten sections were monitored through the Sovasi scale, observing the progressive improvements and promoting - within the group of teachers and through the use of specific support tools - some practices for reflection and redesigning. Finally, the study led to a critical reflection on the evaluation methodology used in order to find new indicators and procedures for devising a new observation tool, complementary and not alternative to the Sovasi Scale. The formative educational evaluation process is proposed as an explorative and qualitative research (Lumbelli, 2006) with a view to the future verification - on a representative sample of kindergarten sections - of the validity of new methodologies for evaluating the quality of kindergartens.